THE USE OF SEAWEED (Eucheuma cottonii)AND TOFU LIQUID AS RAW MATERIAL FOR PRODUCING NATA - Sulastri Sulastri; Tjipto Leksono; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the effect of the different raw materials used in the nata processing to obtain the best nata qualitybased on their sensory, physical, chemical, and microbiologyevaluation.The method used was the experimental and composed as a non-factorial Completely Randomized Design (CRD), with 3 levels of treatment, namely:the using of 100% seaweed filtrate, the using of 100% tofu liquid, and the using of 50% seaweed and 50% tofu liquid.The parameters used in this study were organoleptic test(texture, taste, color, and aroma), physical test (thickness and rendement value, and folding test), proximate composition (the content of water, protein, and crude fiber), and the total aerobic microbes (APC).The results showed that the best nata produced was processed by using 100% seaweed filtrate, characterized by the milky white and attractive appearance, nata tasted in accordance to the raw material used, and was very chewy textured. The best nata product was fulfilled the national quality standard (SNI 01-4317-1996) on nata. It contained 49,1% water, 7,4% protein content, and 37,0% crude fiber content; and was grown by 1,6 x 10 total bacterias.Keywords: nata, seaweed, tofuliquid